Reactive n-species Cahn–Hilliard system: A thermodynamically-consistent model for reversible chemical reactions - Clavijo, S.; Sarmiento, A.; Espath, L.; Dalcin, L.; Cortes, A.; Calo, Victor (Elsevier, 2019)
© 2018 Elsevier B.V. We introduce a multicomponent Cahn–Hilliard system with multiple reversible chemical reactions. We derive the conservation laws of the multicomponent system within the thermodynamical constraints. Furthermore, we consider multiple chemical reactions based on the mass action law. This coupling reproduces phase separation under spinodal decomposition as a chemical reaction between the species takes place. Finally, we perform a numerical simulation to show the robustness of the model as well as the resulting patterns.